2018
DOI: 10.1051/matecconf/201819304023
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of buildings in accordance with the “human-technology-nature” system

Abstract: Reorganization and its variety - building reconstruction - accompanies humanity throughout its highly developed existence. Since the formation of the city, three trends have clearly manifested themselves. The first is the sealing of the building in the center of the city, determined by the presence of ambition and prestige, manifested by the most affluent part of the townspeople who prefer to buy more expensive housing. The second is the expansion of the boundaries of cities near which middle-class people live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The system 'man-technology-environment (MTE)' models functional systems of construction industry, forms their internal 'descriptions' as a compromise of these triads, demonstrates a sufficiently high level of quality of functioning. Therefore, the question of the relationship between the concepts of 'sufficiency' and 'completeness' of the MTE system descriptions is relevant, as well as the construction of a basic infographic model on which these two concepts can be distinguished [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system 'man-technology-environment (MTE)' models functional systems of construction industry, forms their internal 'descriptions' as a compromise of these triads, demonstrates a sufficiently high level of quality of functioning. Therefore, the question of the relationship between the concepts of 'sufficiency' and 'completeness' of the MTE system descriptions is relevant, as well as the construction of a basic infographic model on which these two concepts can be distinguished [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Such an object requires the development of management of the object creation components, which should cover the entire investment and innovative construction project taking into account its social, environmental, engineering and other subsystems. The subject of design is not a general contractor construction organization, but a special organizational structure for the management of the creation and operation of a building object (for example, a developer) that operates throughout the life cycle of the structure as a socio-technical project and includes diagnostic models of technogenic impacts [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Intra-constructional transportation in modern civil engineering in 70% of cases is carried out by means of a road transport on temporary roads and roads arranged for the permanent operation of the building [1,2]. The design of these roads is carried out taking into account special requirements at the stage of preparation of project documentation in the section of the project of the organization of construction.…”
Section: Introductionmentioning
confidence: 99%